2011
DOI: 10.1152/ajpheart.00294.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ sensitization of cardiac myofilament proteins contributes to exercise training-enhanced myocardial function in a porcine model of chronic occlusion

Abstract: Exercise training has been shown to improve cardiac dysfunction in both patients and animal models of coronary artery disease; however, the underlying cellular and molecular mechanisms have not been completely understood. We hypothesized that exercise training would improve force generation in the myocardium distal to chronic coronary artery occlusion via altered intracellular Ca(2+) concentration ([Ca(2+)](i)) cycling and/or Ca(2+) sensitization of myofilaments. Ameroid occluders were surgically placed around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We also determined the time to peak and time to half decay and found these were not altered by alcohol. It should be noted that the time to peak was much higher, and the half time for decay slightly higher than typical times observed in single cells [30, 31]. This is most likely because we determined the 340/380 ratio in a relatively large area, so that the speed at which the calcium transient was transmitted along the length of the vessel strongly influenced these parameters.…”
Section: Discussionmentioning
confidence: 88%
“…We also determined the time to peak and time to half decay and found these were not altered by alcohol. It should be noted that the time to peak was much higher, and the half time for decay slightly higher than typical times observed in single cells [30, 31]. This is most likely because we determined the 340/380 ratio in a relatively large area, so that the speed at which the calcium transient was transmitted along the length of the vessel strongly influenced these parameters.…”
Section: Discussionmentioning
confidence: 88%
“…We found that pharmacologic inhibition or partial genetic ablation of SIRT1 blocked IPC in adult mouse hearts (Nadtochiy et al, 2011; Nadtochiy et al, 2010), suggesting an endogenous role for SIRT1 in protection. Thus, it is possible that age-dependent decline in SIRT1 activity (Braidy et al, 2011) may contribute to loss of IPC.…”
Section: Current Researchmentioning
confidence: 79%
“…For example, the mitochondrial K ATP channel (Wojtovich et al, 2009; Facundo et al, 2006) and sirtuin activity (SIRT1) (Nadtochiy et al, 2011; Nadtochiy et al, 2010) are critical components of IPC, and both exhibit an age-dependent decline in activity (Braidy et al, 2011; Krylova et al, 2006). …”
Section: Ischemic Preconditioning Aging and Mitochondriamentioning
confidence: 99%
See 2 more Smart Citations